Brains on! presents...Meet my micro-pets! - Bloom, Molly, 1983-; Sanchez, Marc, 1970-; Totten, Sanden (Brains on! presents..., 2023)
"It's show-and-tell day, and Dominique can't wait to introduce her awesome pets to the class. They're more helpful than dogs, cuddlier than gerbils, and way smarter than lizards. They're her...MICRO-PETS! As Dominique takes her classmates on a tour through her microbiome, they'll meet some face mites, hang with feet fungi, and visit the fart factory--powered by bacteria in her intestines!" -- Amazon.com.